Meningkatkan Keterampilan membuat Piring Anyaman Lidi melalui Strategi Joyful Learning bagi Anak Tunagrahita Ringan - Fatimah Azzahra; Yarmis Hasan (Universitas Negeri Padang, 2018)
The purpose of this research to find out joyful learning strategies in improving the skill of making woven sticks plate for Mild Intellectually Disabled. The research method use is classroom action research, carried out in the form of collaboration with classroom teachers. Besides the class teacher, student were also include in this study. Student involved in this study amounted two tenth grade mild intellectually disabled children. This research was conducted in two cycles. In the first cycle, observations were made regarding the learning process and the learning outcomes of making woven sticks plate with joyful learning strategies. In the second cycle, observations were made the skills to make woven sticks plate were emphasized in steps students had not mastered. The results of the first cycle students get an average of 70% and 65%. The results of the second cycle students get an average of 87,5% and 84%.